2009
DOI: 10.1016/j.exer.2008.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation and maintenance of gap junctional communication in lens cells

Abstract: The cells of the lens are joined by an extensive network of gap junction intercellular channels consisting of connexins 43, 46, and 50. We have proposed, and experimentally supported, the hypothesis that fibroblast growth factor (FGF) signaling is required for upregulation of gap junction–mediated intercellular coupling (GJIC) at the lens equator. The ability of FGF to increase GJIC in cultured lens cells requires sustained activation of extracellular signal-regulated kinase (ERK). In other cell types, activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 91 publications
(120 reference statements)
1
35
0
Order By: Relevance
“…Cx46 mRNA expression was also linked with improved survival in ER positive patients which, however, was preserved also in ER negative patients, suggesting a reciprocal regulation of Cx46 compared to Cx43 expression in this subgroup. This is in line with data gained in lens cell cultures showing the simultaneous down-regulation of Cx43 and upregulation of Cx46 expression by the tumor promoter phorbol ester (12-O-tetradecanoylphorbol-13-acetate) [53] or by the activation of the MAPK/ERK pathway [54]. Differential regulation of connexin isotypes are rather common and allows connexins to serve either as conditional tumor suppressors in primary cancer or tumor supporters in advanced, metastatic cases [30], [32], [33], [51].…”
Section: Discussionsupporting
confidence: 90%
“…Cx46 mRNA expression was also linked with improved survival in ER positive patients which, however, was preserved also in ER negative patients, suggesting a reciprocal regulation of Cx46 compared to Cx43 expression in this subgroup. This is in line with data gained in lens cell cultures showing the simultaneous down-regulation of Cx43 and upregulation of Cx46 expression by the tumor promoter phorbol ester (12-O-tetradecanoylphorbol-13-acetate) [53] or by the activation of the MAPK/ERK pathway [54]. Differential regulation of connexin isotypes are rather common and allows connexins to serve either as conditional tumor suppressors in primary cancer or tumor supporters in advanced, metastatic cases [30], [32], [33], [51].…”
Section: Discussionsupporting
confidence: 90%
“…First, the ERK pathway has been shown to regulate Cx43 expression and function. ERK activation has been shown to up‐regulate Cx43 expression in several cell types (Cushing et al, 2005; Jia et al, 2008; Boswell et al, 2009). Activation of ERK has been shown to phosphorylate Cx43 at multiple serine residues in the C‐terminal tail and has been shown to regulate Cx43 function, typically inhibiting GJIC (Warn‐Cramer et al, 1998; Lampe and Lau, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Of more physiological relevance, the coupling conductance is significantly increased by fibroblast growth factor (FGF), and FGF is present in the vitreous humor (110). More recently, it has been shown that FGF requires bone morphogenic protein (BMP) signaling to induce an increase in coupling conductance, that expression of BMP receptors is high in the equatorial DF of the lens, and that BMP is released by the lens through an autocrine system (26). These observations led the authors to suggest the relatively high coupling conductance between equatorial DF is regulated by BMP and FGF.…”
Section: The Mature Lensmentioning
confidence: 99%